2010
DOI: 10.1074/jbc.m110.102079
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Type I Collagen Homotrimer Resistance to Mammalian Collagenases

Abstract: Type I collagen cleavage is crucial for tissue remodeling, but its homotrimeric isoform is resistant to all collagenases. The homotrimers occur in fetal tissues, fibrosis, and cancer, where their collagenase resistance may play an important physiological role. To understand the mechanism of this resistance, we studied interactions of α1(I)3 homotrimers and normal α1(I)2α2(I) heterotrimers with fibroblast collagenase (MMP-1). Similar MMP-1 binding to the two isoforms and similar cleavage efficiency of unwound α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
109
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(122 citation statements)
references
References 46 publications
11
109
0
2
Order By: Relevance
“…Homotrimeric type I collagen (␣1(I) 3 ) is much less susceptible to MMP-1 hydrolysis than heterotrimeric type I collagen, and the effect is not due to binding (45). The homotrimer is more thermally stable than the heterotrimer by ϳ2.5°C and melts 100 times slower (46,47).…”
Section: Unique Features Of Interstitial Collagen Cleavage Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Homotrimeric type I collagen (␣1(I) 3 ) is much less susceptible to MMP-1 hydrolysis than heterotrimeric type I collagen, and the effect is not due to binding (45). The homotrimer is more thermally stable than the heterotrimer by ϳ2.5°C and melts 100 times slower (46,47).…”
Section: Unique Features Of Interstitial Collagen Cleavage Sitesmentioning
confidence: 99%
“…The microunfolding patterns of the two collagen subtypes are different (47). Thus, the difference between MMP-1 activity toward homotrimeric versus heterotrimeric type I collagen is due to local triple-helical unwinding at the cleavage site (45). The ␣2(I) chain also increases hydrophobicity compared with the ␣1(I) chain, driving out structured water and facilitating hydrolysis (46).…”
Section: Unique Features Of Interstitial Collagen Cleavage Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another enigma of collagenolysis became apparent when the crystal structures of MMP-1Cat (8-10), 12), and full-length pig MMP-1 (6) were solved: The catalytic cleft of these enzymes is too narrow to accommodate collagen in its native triple-helical conformation. A number of hypotheses have been proposed to explain how collagenases may destabilize and cleave triple-helical collagen (13-16), and we have experimentally demonstrated that MMP-1 unwinds triple-helical collagen locally before peptide bond hydrolysis (17,18). A recent study mapped the interaction sites in MMP-1 and in triple-helical collagen by using NMR and proposed a model of collagen binding and unwinding (19).…”
mentioning
confidence: 99%
“…Contrary to homozygous COL1A1 null mutations that are most likely incompatible with life as seen in the Mov13 mice, patients with homozygous COL1A2 null mutations have a phenotype more similar to EDS (Malfait et al, 2006;Nicholls et al, 2001;Schwarze et al, 2004). They synthesize a(I) 3 homotrimers which were shown to be overmodified, to alter the triple helical structure and to resist collagenases digestion (Deak et al, 1985;Han et al, 2010;Kuznetsova et al, 2001). Collagen structural mutations instead often have a profound impact on procollagen chains register and assembly and may slow down the winding of the triple helix resulting in overmodification of additional proline and lysine residues by ER resident enzymes (i.e.…”
Section: Pathogenesis and Disease Mechanisms In Oimentioning
confidence: 99%